2020
DOI: 10.21608/asejaiqjsae.2020.91325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Water Stress on Growth, Productivity and Powdery Mildew Disease of Ten Sugar beet Varieties

Abstract: Powdery mildew is a fungal disease that causes a serious reduction in both root and sugar yields in sugar beet areas in Egypt. This study aimed to determine the effect of three water stress treatments namely, IR1 (recommended irrigation times), IR2 (3 withholding irrigation times), and IR3 (4withholding irrigation times) on powdery mildew infection severity and yield components of ten sugar beet varieties. The experimental design was a split-plot design with three replications at Al-Fayoum Governorate, (29°17ˋ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
1
0
0
Order By: Relevance
“…This observation may be referred to the gene make-up among varieties and their response to the environmental conditions. Similar tendency was observed by Ahmed et al (2017), Thalooth et al (2019 and Abu-Ellail and El-Mansoub (2020). D. Significant interaction effects: 1.…”
Section: B Quality Parameterssupporting
confidence: 85%
“…This observation may be referred to the gene make-up among varieties and their response to the environmental conditions. Similar tendency was observed by Ahmed et al (2017), Thalooth et al (2019 and Abu-Ellail and El-Mansoub (2020). D. Significant interaction effects: 1.…”
Section: B Quality Parameterssupporting
confidence: 85%
“…Moreover, the results showed that the relative increase percentages due to application 10 ton/fad were 86.65, 71.91 and 72.02 % for the three seasons, respectively compared with 0 ton/fad organic fertilization. Harmony discoveries were made by (Abd El-Aziz and El Sahed., 2021;El-Mansoub, 2020 andAbou-Elwafa et al, 2020).…”
Section: Sugar Yield (Kg/fad)mentioning
confidence: 99%
“…Sugar beet plants treated with Bellis produced higher peroxidase and phenol oxidase than the control. The resistance has been associated with a high activity of defensive enzymes such as peroxidase (Farrag and El-Mansoub, 2020).…”
Section: Effect Of Some Fungicides On Sugar Beet Yield and Qualitymentioning
confidence: 99%